TREATMENT OF PRESSURE ULCERS WITH BIOAPIFIT® WOUND HEALING HERBAL OINTMENT - A PRELIMINARY STUDY - Oreščanin, Višnja (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Objectives: The purpose of this work was development, formulation and testing of new herbal ointment for the treatment of pressure ulcers. Patients and methods: 50 patients (27 males and 23 females) with total 84 ulcers of stage II and III were treated 28 days (twice a day) with the ointment containing the following ingredients: Symphytum officinale, Plantago major, Calendula officinalis, Matricaria chamomilla, Bellis perennis, Achillea millefolium, Salvia officinalis, Hypericum perforatum, Olea europaea, Lavandula officinalis, Melaleuca alternifolia, Cympobogon martini, Origanum vulgare, Eugenia caryophyllata, Thymus vulgaris ct. thymol, Cera alba, honey, and glycerol. The healing process was assessed by Pressure Ulcer Scale for Healing (PUSH) tool ver. 3.0. Results: Prior to the therapy mean value and standard deviation of the PUSH score for ulcer surface area, quantity of exudate, type of tissue and the total score were 8.39±0.79, 1.35±0.84, 2.81±0.40 and 12.5±1.94, respectively. All the mentioned values decreased significantly after only seven days of the treatment (p<0.00001). Further treatment resulted in linear decrease of PUSH parameters reaching zero values after 28 days of the therapy. Slough disappeared after 14 days of the therapy and epithelial tissue was obtained on the edge of 67.86% of the ulcers. Following the 21 day of the treatment 17.86% of the ulcers were completely closed while after 28 days all the ulcers healed completely. Conclusion: Four weeks of the topical treatment with Bioapifit® herbal wound healing ointment resulted in complete closure of all ulcers with mean healing time of 26.4 days. Such excellent results could be attributed to the ointment’s formulation containing the ingredients with strong wound healing, anti-inflammatory and antimicrobial potential.